Continuous feeding of antistatic agents for gas phase polymerization processes

By reacting an antistatic agent with an alkyl aluminum to form an antistatic compound, the problem of the existing antistatic agent inhibiting the catalyst activity and being unable to effectively prevent particle accumulation during the gas phase polymerization process is solved, achieving a more effective antistatic effect and achieving better performance in the gas phase polymerization process. Use in highly regulated applications.

CN113382999BActive Publication Date: 2025-01-21BRASKEM SA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980087017.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-28
Filing Date
2019-12-28
Publication Date
2025-01-21
Estimated Expiration
2039-12-28

AI Technical Summary

Technical Problem

In the process of gas-phase polymerization, existing antistatic agents not only fail to effectively prevent polymer particles from accumulating, but also inhibit the activity of polymerization catalysts, and there are limitations on use in highly regulated applications.

Method used

By reacting an antistatic agent with an alkyl aluminum to form an antistatic compound, it can be used to improve the antistatic effect and reduce inhibition of catalyst activity, thereby effectively preventing particle accumulation during the polymerization process.

Benefits of technology

A balance is achieved between maintaining catalytic activity and preventing solids accumulation in the reactor, providing a more effective antistatic effect and allowing use in highly regulated applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003136738410000101
    Figure BDA0003136738410000101
  • Figure BDA0003136738410000111
    Figure BDA0003136738410000111
  • Figure BDA0003136738410000112
    Figure BDA0003136738410000112
Patent Text Reader

Abstract

The method may include reacting an antistatic agent with at least one aluminum alkyl to form an antistatic complex, and may further include feeding the antistatic complex into a polymerization process. The method of using an antistatic agent in a polymerization process may include feeding the antistatic agent into the polymerization process and then reacting the antistatic agent with at least one aluminum alkyl.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Gas phase polymerization is a common process for the efficient preparation of various polymers. Specifically, gas phase polymerization can be used to efficiently prepare homopolymers of light olefins such as ethylene or propylene and copolymers of ethylene and / or propylene with C4-C8 α-olefins.

[0002] Reactors for gas phase polymerization typically include a fluidized bed consisting of polymer particles polymerized in the presence of a gas mixture. It is generally advantageous to fluidize the bed because it provides an extremely high surface area to maximize contact between the bed and the gas mixture. In addition, a fluidized bed allows complete mixing of the particle phase and more frequent collisions between polymer particles and between polymer particles and the reactor wall.

[0003] However, these frequent particle-particle and particle-wall collisions may result in the formation of electrostatic charges, which may result in electrostatic attraction between polymer particles and the reactor walls. This may result in the accumulation of solid matter in the reactor, commonly referred to as "sheeting" or "chunking". These phenomena may result in polymer solid matter negatively affecting the polymerization process by interfering with fluidization, affecting gas flow, blocking product outlets. Such results may reduce the efficiency and reliability of the polymerization and force reactor shutdown for cleaning.

[0004] Such solid accumulation can be prevented by using antistatic agents, which can limit the formation of electrostatic charge and maintain the fluidization of the reactor bed. Typically, antistatic agents include compounds containing polar functional groups such as hydroxyl, ester, ether, alkyl, alkoxy, aryloxy, siloxy, silane or sulfonate groups.

[0005] For example, European Patent No. 1 255 783 B1 describes a method for introducing a carboxylic acid metal salt into a polymerization reactor to reduce the level of fouling and sheeting to maintain smooth operation of a continuous polymerization process. U.S. Patent No. 8,017,703 B2 describes a method for continuously feeding a polyglycerol ester into a polymerization reactor and suppressing the generation of inhomogeneity.

[0006] Other examples include U.S. Patent Publication No. 2012 / 0283369 A1, which describes a method for polymerizing olefins in the presence of an antistatic agent, wherein the antistatic agent is a composition comprising a polysulfone copolymer, a polymeric compound containing a basic nitrogen atom, an oil-soluble sulfonic acid and a solvent. U.S. Patent No. 8,865,847 B2 describes a method for polymerizing ethylene and optional alpha-olefins in the presence of an antistatic continuity additive, the antistatic continuity additive comprising a dialkanolamide, an oil-soluble sulfonic acid and a dialkanolamine derived from a fatty acid. European Patent Application No. 3 034 519 A1 describes a gas phase method for olefin polymerization, wherein an ester of a fatty acid and a polyol is used as an antistatic agent, the polyol being selected from the group consisting of the following: C4-C6 sugar alcohol, dehydrated C4-C6 sugar alcohol and C4-C6 monosaccharide.

[0007] However, most antistatic agents are known to negatively affect the activity of olefin polymerization catalysts. This limits the amount of antistatic agent that can be used, thus resulting in a compromise between maintaining catalytic activity and effectively preventing solid accumulation in the reactor.

[0008] The use of antistatic agents to prepare polymers for food contact applications is further limited by restrictions that have been implemented by government regulatory agencies such as the European Commission and the US Food and Drug Administration. Restricted compounds include ethoxylated amines, alkylbenzene sulfonic acids, random ethylene oxide / propylene oxide copolymers, etc.

[0009] Therefore, there is a need for effective antistatic agents which not only prevent polymer particle accumulation but also do not inhibit the catalytic activity of common polymerization catalysts and allow for use in highly regulated applications such as in the food and pharmaceutical industries. Summary of the invention

[0010] This Summary is provided to introduce a selection of concepts that are further described below in the Detailed Description. This Summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used as an aid in limiting the scope of the claimed subject matter.

[0011] In one aspect, embodiments disclosed herein are directed to methods that can include reacting an antistatic agent with at least one aluminum alkyl to form an antistatic complex.

[0012] In another aspect, embodiments disclosed herein relate to methods of using an antistatic agent in a polymerization process. Such methods may include feeding the antistatic agent into the polymerization process and then reacting the antistatic agent with at least one aluminum alkyl.

[0013] In another aspect, embodiments disclosed herein relate to polymers prepared by a process that may include feeding an antistatic agent into a polymerization process and then reacting the antistatic agent with at least one aluminum alkyl.

[0014] In another aspect, embodiments disclosed herein relate to an antistatic composite formed by a method that may include reacting an antistatic agent with at least one aluminum alkyl.

[0015] Other aspects and advantages of the claimed subject matter will be apparent from the following description and appended claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a flow chart illustrating a method of using an antistatic agent in a polymerization process according to one or more embodiments of the present invention.

[0017] Figure 2 is a flow chart illustrating a method of using an antistatic agent in a polymerization process according to one or more embodiments of the present invention.

[0018] Figure 3 The conductivity of various antistatic agents and composites is shown.

[0019] Figure 4 Simulation of the monoester of oleic acid and oxybis(propylene glycol) is shown 1 H NMR spectrum.

[0020] Figure 5 The antistatic composites of various compounds comprising monoesters of oleic acid and oxybis(propylene glycol) are shown. 1 H NMR spectrum.

[0021] Figure 6 A photograph of a single phase resulting from the reaction of the monoester of oleic acid and oxybis(propylene glycol) with tributylaluminum is shown.

[0022] Figure 7 A photograph of two phases resulting from the reaction of the monoester of oleic acid and oxybis(propylene glycol) with triethylaluminum is shown. DETAILED DESCRIPTION

[0023] In one aspect, embodiments disclosed herein relate to methods for preparing antistatic compounds. In one or more embodiments, the method may involve reacting the antistatic compound with at least one alkyl aluminum. Another aspect of the disclosed embodiments relates to an antistatic compound prepared by such a method.

[0024] In another aspect, embodiments disclosed herein relate to the use of an antistatic agent in a polymerization process. In one or more embodiments, the method according to the present invention may involve reacting an antistatic agent with one or more compounds such as an aluminum alkyl to provide an antistatic complex that can be subsequently fed into a polymerization process. In other embodiments, the method according to the present invention may involve first feeding an antistatic agent into a polymerization process, and then reacting the antistatic agent with one or more compounds such as an aluminum alkyl to provide an antistatic complex in situ. Another aspect of the disclosed embodiment relates to a polymer prepared by such a method.

[0025] Typical antistatic agents may be unfavorable for polymerization process because they may negatively affect the activity of polymerization catalyst. In such a case, this means that the amount of the antistatic agent used must be limited, thereby limiting its efficacy. The antistatic agent reacted with alkyl aluminum can be used according to the method disclosed herein. Such a method can be advantageous for a typical process because they can provide an improved antistatic effect, and can hinder the activity of polymerization catalyst to a lower degree compared with other antistatic agents. In addition, the method according to the present invention can use an antistatic agent that is not limited to, for example, food contact applications.

[0026] Method for forming antistatic composite

[0027] Methods according to one or more embodiments of the present disclosure may include reacting at least one antistatic agent with at least one aluminum alkyl to form an antistatic complex. In further embodiments, the antistatic complex may be used during the polymerization process.

[0028] In the method of one or more embodiments, the molar ratio of the amount of the reacted antistatic agent relative to the amount of the alkyl aluminum is in the range of about 1: 1 to about 1: 200. In other embodiments, the molar ratio of the amount of the antistatic agent relative to the amount of the alkyl aluminum is in the range of from a lower limit of any one of 1: 1, 1: 10, or 1: 50 to an upper limit of any one of 1: 100, 1: 150, or 1: 200, wherein any lower limit can be used in combination with any upper limit.

[0029] The method can use any aluminum alkyl or combination thereof, but in some embodiments, the aluminum alkyl can be specifically a trialkyl aluminum. In one or more embodiments, the aluminum alkyl is one or more of triethyl aluminum and triisobutyl aluminum.

[0030] Any antistatic agent known in the art can be used according to the method for one or more embodiments. However, in the method for multiple embodiments, the antistatic agent is specifically a fatty acid ester. For example, the fatty acid ester can be formed by a saturated or unsaturated fatty acid of C6 to C26 or in a more specific embodiment of C12 to C22. In a specific embodiment, such a fatty acid can be reacted with a polyol such as glycerol. However, it should also be understood that the polyol can have one or more acids reacted therewith, including but not limited to fatty acids. For example, it should be understood that one or more of the ester groups formed will be formed with organic acids such as acetic acid, citric acid or other shorter organic acids that are not fatty acids. Fatty acid esters can be used in any suitable form, such as used in a solid state, or mixed with a liquid carrier.

[0031] In one or more embodiments, the method according to the present disclosure can use antistatic agents approved by government regulatory agencies for specific applications (such as one or more of the food and pharmaceutical industries). In one or more embodiments, the antistatic agent is an antistatic agent listed in 21C.FR178.3130 approved by the U.S. Food and Drug Administration for food packaging materials. The fatty acid ester used in one or more embodiments can be, for example, Grindsted PGE O 80D or Grindsted PS432 (both sold by DuPont) or Cithrol GMS90 (sold by Croda).

[0032] The method for forming an antistatic composite according to one or more embodiments may involve, before reacting the antistatic agent with the alkyl aluminum, optionally mixing the antistatic agent with at least one hydrocarbon compound. In some embodiments, the hydrocarbon compound may be a C3-C6 hydrocarbon, and may be linear or branched. The hydrocarbon may be saturated, and in some embodiments, may be selected from propane, butane, isobutylene, pentane, isopentane, hexane, heptane, etc. The hydrocarbon may be unsaturated, and in some embodiments, may be selected from propylene, butylene, isobutylene, pentene, isopentene, etc. The hydrocarbon may be specifically liquid.

[0033] In some embodiments, the antistatic agent is mixed with the hydrocarbon compound at a mass ratio in the range of about 1: 10 to about 9: 10 relative to the amount of the hydrocarbon compound. In some embodiments, the antistatic agent and the hydrocarbon compound may be mixed together using a continuous stirred tank reactor or an in-line mixer.

[0034] Antistatic Compound

[0035] The antistatic composite according to one or more embodiments of the present disclosure can be prepared by any of the methods described in detail above. In one or more embodiments, the antistatic composite can be formed by the reaction of an antistatic agent with an alkyl aluminum. In some embodiments, the antistatic composite is more effectively limited to static electricity accumulation and prevents particle accumulation compared to unreacted antistatic agents. In some embodiments, the antistatic composite can be advantageous because it does not inhibit the catalytic activity of the polymerization catalyst.

[0036] The antistatic composite of one or more embodiments may include an antistatic agent, one or more aluminum alkyls, and at least one product of a reaction between the antistatic agent and the aluminum alkyl. In embodiments where the antistatic agent is a fatty acid ester, the reaction product may include one or more aluminum alkyls different from the aluminum alkyl reacted with the antistatic agent, and / or a compound that may be defined as an aluminum soap, such as aluminum stearate.

[0037] The antistatic composite composition of one or more embodiments may also include at least one hydrocarbon compound. The hydrocarbon may be a C3-C6 hydrocarbon, and may be linear or branched. The hydrocarbon may be saturated, and in some embodiments, may be selected from propane, butane, isobutylene, pentane, isopentane, hexane, heptane, etc. The hydrocarbon may be unsaturated, and in some embodiments, may be selected from propylene, butylene, isobutylene, pentene, isopentene, etc. The hydrocarbon may be specifically liquid.

[0038] Use of antistatic agents during polymerization

[0039] The antistatic agents and antistatic compounds detailed above may be used during the polymerization process. In one or more embodiments, the antistatic compounds may limit charging of polymer particles and prevent the resulting accumulation of polymer solid matter that may negatively impact the efficiency and reliability of the polymerization.

[0040] The method of using an antistatic agent in a polymerization process according to one or more embodiments may involve at least a feeding step of feeding the antistatic agent (or antistatic compound) into the polymerization process and a step of reacting the antistatic agent with at least one alkyl aluminum. The method of one or more embodiments may also include a step of mixing the antistatic agent with a hydrocarbon compound. The order of these steps is not particularly limited and may be any order suitable for the target process.

[0041] Figure 1A method for using an antistatic agent in a polymerization process according to one or more embodiments of the present disclosure is shown. In which, the antistatic agent 100 can be mixed with a hydrocarbon compound 101 in a mixing step 110. As detailed above, the resulting mixture can then be reacted with an alkyl aluminum 102 to obtain an antistatic complex 111. A feeding step 112 can then feed the antistatic complex into a polymerization process 113. In some embodiments, the antistatic agent is not mixed with the hydrocarbon, but is directly reacted with the alkyl aluminum 102 to obtain the antistatic complex 111, which is then fed 112 into the polymerization process 113.

[0042] Figure 2 Another method of using an antistatic agent in a polymerization process according to one or more embodiments of the present disclosure is shown. Therein, an antistatic agent 200 can be mixed with a hydrocarbon compound 201 in a mixing step 210. The resulting mixture can then be fed 212 into a polymerization process 213. Subsequent reaction of the antistatic agent with an aluminum alkyl 202 results in an in-situ generated antistatic complex 211. In some embodiments, the antistatic agent is not mixed with the hydrocarbon, but is directly fed 212 into the polymerization process 213 and then reacts with the aluminum alkyl 202 to produce the antistatic complex 211.

[0043] Feed

[0044] Any suitable device known in the art can be used to carry out the feeding step of the method according to one or more embodiments. In a specific embodiment, a valveless pump can be used. In some embodiments, the valveless pump can be a piston pump. In one or more embodiments, the feeding step can be carried out continuously during the polymerization process.

[0045] The feeding step can feed the antistatic compound or antistatic agent to any suitable stage of the polymerization process. In one or more embodiments, the antistatic compound or antistatic agent can be fed into the polymerization process at one or more of a gas phase reactor, a loop reactor, a discharge reactor line, a gas phase recycle line, a bag filter, or a heat exchanger used to carry out the polymerization process.

[0046] In one or more embodiments, the feeding step is performed at a rate proportional to the polymer production rate. In some embodiments, the antistatic compound or antistatic agent is fed to the polymerization process at a rate in an amount ranging from about 5 to 1000 ppm by weight relative to the polymer production rate.

[0047] Polymerization process

[0048] The polymerization process of the method according to one or more embodiments is not particularly limited. However, in one or more embodiments, the polymerization process may specifically be a gas phase polymerization.

[0049] In one or more embodiments, polymerization process can make at least one or more polymerizations in ethylene, propylene, butene and hexene. In some embodiments, polymerization process produces homopolymer. The homopolymer produced by the method for one or more embodiments can be one of polypropylene and polyethylene. In some embodiments, polymerization process produces copolymer. The copolymer produced by the method for one or more embodiments can be one of polypropylene random copolymer, polypropylene heterophasic copolymer, polypropylene terpolymer and linear low density polyethylene.

[0050] In some embodiments, the polymerization process may use a metallocene or Ziegler-Natta catalyst. The Ziegler-Natta and metallocene catalysts of one or more embodiments are not limited and may be any Ziegler-Natta or metallocene catalyst known to those of ordinary skill in the art. The Ziegler-Natta catalyst may be a transition metal salt, wherein the transition metal is selected from Groups 4-12. Some Ziegler-Natta catalysts may also be used in combination with MgCl 2 and / or TiCl 4 The metallocene catalyst of one or more embodiments may be Cp * 2 MCl 2 Type dichloride complexes, where M is a transition metal such as Ti, Zr and Hf, and Cp * is a substituted or unsubstituted cyclopentadienyl anion.

[0051] In one or more embodiments, the polymerization process may include the use of any suitable apparatus or device known in the art. In some embodiments, the polymerization process may include the use of one or more of the following: a continuous stirred tank polymerization reactor, a loop polymerization reactor, a fluidized bed polymerization reactor, and a plug flow polymerization reactor.

[0052] In one or more embodiments, the polymerization process can utilize one or more gas phase reactors. In some embodiments, the polymerization process can utilize a gas phase reactor in combination with one or more of a slurry reactor and a bulk reactor.

[0053] polymer

[0054] The polymer according to one or more embodiments of the present disclosure can be prepared by any of the methods described in detail herein. As mentioned above, the polymer of one or more embodiments can include monomers derived from one or more of ethylene, propylene, butene and hexene. In some embodiments, the polymer can be a homopolymer, and in some embodiments, the homopolymer can be one of polypropylene and polyethylene. In one or more embodiments, the polymer can be a copolymer, and in some embodiments, the copolymer can be one of polypropylene random copolymer, polypropylene multiphase copolymer, polypropylene terpolymer and linear low density polyethylene.

[0055] Example

[0056] The following examples are illustrative only and should not be construed as limiting the scope of the present disclosure.

[0057] Embodiment 1:

[0058] The conductivity of a compound is an important property that determines whether the compound can be used successfully as an antistatic agent (or antistatic compound) in the polymerization process and whether the electrostatic charge generated during the polymerization can be compensated. The conductivity of Grindsted PS 432 (Dupont) (referred to as "GE" herein) and a mixture of triethylaluminum / Grindsted PS432 (TEAL / GE) and triisobutylaluminum / Grindsted PS432 (TIBAL / GE) in a ratio of 1:1 and 10:1 mol / mol was measured using a digital conductivity meter model 1152 provided by EMCEEElectronics.

[0059] GE contains two main substances: the monoester of oleic acid with oxybis(propylene glycol) (CAS No. 49553-76-6); and the acetate ester of monoglyceride (CAS No. 736150-63-3).

[0060] pass 1 H NMR (Agilent 400Mhz, with DD2 console equipped with OneNMR probe) studies the antistatic complexes formed by the reaction of oleic acid monoesters with complexes of oxybis(propylene glycol) / triisobutylaluminum or oxybis(propylene glycol) / triethylaluminum. Samples were prepared using deuterated cyclohexane in 5 mm tubes. The monoester of oleic acid and oxybis(propylene glycol) was diluted at a ratio of 10 mg relative to 0.6 mL deuterated cyclohexane. The reactions of oleic acid and the monoester of oxybis(propylene glycol) / triisobutyl-aluminum and the monoester of oleic acid and oxybis(propylene glycol) / triethyl-aluminum were carried out in a 1:1 molar ratio.

[0061] Before starting the measurement, the reliability of the conductivity meter was confirmed by measuring cyclohexane, which provides zero conductivity. The solutions were prepared in the glove box, dilutions of the antistatic agent in high purity hexane were performed, and the concentrations are expressed in ppm wt. Pure Grindsted PS432 showed lower conductivity than the Grindsted PS432 / Alkylaluminum mixture. Figure 3 As shown, the formation of antistatic complexes improves the conductivity.

[0062] The antistatic compound formed by the reaction of monoester / triisobutylaluminum reaction of oleic acid and oxygen bis (propylene glycol) is only shown as one phase. The antistatic compound formed by the reaction of monoester / triethylaluminum reaction of oleic acid and oxygen bis (propylene glycol) is shown as two phases: white solid and liquid. These two phases are separated, and each part of 10mg is diluted in the deuterated cyclohexane of 0.6mL. The NMR spectrum of the monoester of oleic acid and oxygen bis (propylene glycol) is simulated in the software Predict that Universidad del Valle (Cali-Colombia) provides, and identifies the hydrogen peak.

[0063] use Figure 4 The simulated spectra provided in the paper serve as a basis for understanding Figure 5 Shown in NMR analysis.The spectrum of the homogeneous liquid phase obtained by the reaction of the monoester / triisobutylaluminum of oleic acid and oxygen bis (propylene glycol) demonstrates the formation of antistatic complex.Different from groups A, C, DE, F, GH, I and J, do not detect group B, which shows that triisobutylaluminum may react with the hydroxyl existing on the group C.The spectrum of the solid phase obtained by the reaction of the monoester / triethylaluminum of oleic acid and oxygen bis (propylene glycol) demonstrates the formation of antistatic complex, and does not clearly detect groups B, C, D and E.The homogeneous liquid phase does not contain group B, shows that the molecule of the monoester of oleic acid and oxygen bis (propylene glycol) is degraded at this carbon.Groups C, D and E are detected in the liquid phase spectrum.

[0064] Conductivity analysis and NMR analysis showed that the interactions of oxybis(propylene glycol) / triisobutylaluminum and oxybis(propylene glycol) / triethylaluminum were different, resulting in different antistatic complexes.

[0065] Figure 6 Shown is a single phase prepared by the reaction of oleic acid with the monoester of oxybis(propylene glycol) / triisobutylaluminum. Figure 7 Shown are two phases formed by the reaction of oleic acid with the monoester of oxybis(propylene glycol) / triethyl-aluminum.

[0066] Embodiment 2:

[0067] In a fluidized bed gas phase reactor, 36 kg / h of high density polyethylene (HDPE) was produced by polymerizing ethylene using a Ziegler-Natta catalyst, triethyl-aluminum (TEAL) as a cocatalyst and cyclohexyl-methyl-dimethoxysilane as an external donor in the presence of hydrogen as a molecular weight regulator, butene as a density regulator, C3-C6 saturated hydrocarbons as an inert diluent and Atmer 163 (ethoxylated amine) as an antistatic agent. In the fluidized bed gas phase reactor, the operating conditions of Table 1 were met.

[0068] Table 1: Conditions of Example 2

[0069]

[0070] The total amount of Atmer 163 introduced into the polymerization reactor was 930 ppm by weight based on the production rate.

[0071] The obtained HDPE had a melt flow index of 12.0 (g / 10 min) at 190° C. and a density of 0.952 g / cc at 23° C. In this polymerization run, continuous discharge of HDPE was observed, and the formation of lumps was prevented.

[0072] Embodiment 3:

[0073] High density polyethylene was repeated according to similar operating conditions of Example 2 to evaluate Grindsted PS432 (acetic acid ester of monoester of oleic acid and oxybis(propylene glycol) / monoglyceride).

[0074] In a fluidized bed gas phase reactor, 36 kg / h of high density polyethylene (HDPE) was produced by polymerizing ethylene using a Ziegler-Natta catalyst, triethyl-aluminum (TEAL) as a cocatalyst and cyclohexyl-methyl-dimethoxysilane as an external donor in the presence of hydrogen as a molecular weight regulator, butene as a density regulator, C3-C6 saturated hydrocarbons as an inert diluent and Grindsted PS432 (acetic ester of monoester of oleic acid and monoglyceride of oxybis(propylene glycol)). In the fluidized bed gas phase reactor, the operating conditions of Table 2 were met:

[0075] Table 2: Conditions of Example 3

[0076]

[0077] The total amount of Grindsted PS432 introduced into the polymerization reactor was 650 ppm by weight based on the production rate.

[0078] The resulting HDPE had a melt flow index of 12.0 (g / 10 min) at 190°C and a density of 0.953 g / cc at 23°C.

[0079] In this polymerization run, continuous discharge of HDPE was observed and the formation of agglomerates was prevented.

[0080] Table 3 shows the performance of Grindsted PS432 compared with Atmer 163 when triethylaluminum was used as a polymerization cocatalyst:

[0081] Table 3: GE (Example 3) relative to Atmer163 (Example 2)

[0082]

[0083] Embodiment 4:

[0084] 21,000 to 32,000 kg / h of polypropylene heterophasic copolymer (HECO) was prepared by polymerizing propylene-ethylene in a fluidized bed gas phase reactor using a Ziegler-Natta catalyst, triethyl-aluminum (TEAL) as a cocatalyst and diisopropyl-dimethoxysilane as an external donor in the presence of hydrogen as a molecular weight regulator and Atmer 163 (ethoxylated amine) as an antistatic agent. In the fluidized bed gas phase reactor, the following operating conditions were met:

[0085] Table 4: Conditions of Example 4

[0086]

[0087]

[0088] The total amount of Atmer 163 introduced into the polymerization reactor was 120 ppm by weight based on the production rate.

[0089] The obtained HECO has a melt flow index at 230° C. of 1.0 to 20.0 (g / 10 min) and 3.0 to 20.0 wt % of bound ethylene.

[0090] In this polymerization run, continuous discharge of HECO was observed and the formation of agglomerates was prevented.

[0091] Embodiment 5:

[0092] The preparation of a polypropylene heterophasic copolymer (HECO) was repeated according to similar operating conditions of Example 4 to evaluate Grindsted PS432 (acetic acid ester of monoester of oleic acid and oxybis(propylene glycol) / monoglyceride).

[0093] In a fluidized bed gas phase reactor, 24,400 kg / h of polypropylene heterophasic copolymer (HECO) was prepared by polymerizing propylene-ethylene using a Ziegler-Natta catalyst, triethyl-aluminum (TEAL) as a cocatalyst and diisopropyl-dimethoxysilane as an external donor in the presence of hydrogen as a molecular weight regulator and Grindsted PS432 (acetic ester of monoester of oleic acid and monoester of oxybis(propylene glycol) / monoglyceride) as an antistatic agent. In the fluidized bed gas phase reactor, the operating conditions of Table 5 were met.

[0094] Table 5: Conditions of Example 5

[0095]

[0096] The total amount of Grindsted PS432 introduced into the polymerization reactor was 50 ppm by weight based on the production rate. The obtained HECO had a melt flow index at 230° C. of 1.0 to 20.0 (g / 10 min) and a bound ethylene of 3.0 to 20.0 wt. In this polymerization run, continuous discharge of HECO was observed and the formation of lumps was prevented.

[0097] Table 6 shows the performance of Grindsted PS432 compared to Atmer 163 when triethylaluminum was used as a polymerization cocatalyst:

[0098] Table 6: GE (Example 5) relative to Atmer163 (Example 4)

[0099]

[0100] Embodiment 6:

[0101] 50 kg / h of high density polyethylene (HDPE) was produced by polymerizing ethylene in a fluidized bed gas phase reactor using a Ziegler-Natta catalyst, triisobutyl-aluminum (TIBAL) as a cocatalyst and tetrahydrofuran as an external donor in the presence of hydrogen as a molecular weight regulator, butene as a density regulator, C3-C6 saturated hydrocarbons as an inert diluent and Grindsted PS432 (acetic ester of monoester of oleic acid and oxybis(propylene glycol) / monoglyceride) as an antistatic agent. In the fluidized bed gas phase reactor, the following operating conditions were met:

[0102] Table 7: Conditions of Example 6

[0103]

[0104] The total amount of Grindsted PS432 introduced into the polymerization reactor was 607 ppm by weight based on the production rate. The obtained HDPE had a melt flow index of 21.1 (g / 10 min) at 190° C. and a density of 0.958 g / cc at 23° C. In this polymerization run, continuous discharge of HDPE was observed and the formation of lumps was prevented.

[0105] Although only some exemplary embodiments are described in detail above, it will be readily understood by those skilled in the art that a variety of changes are feasible in the exemplary embodiments without substantially departing from the present invention. Therefore, all such changes are intended to be included within the scope of the present disclosure as defined in the appended claims. In the claims, means plus function statements are intended to cover structures described herein as performing the functions described, and not only structural equivalents, but also equivalent structures. Therefore, although nails and bolts may not be structural equivalents because nails use cylindrical surfaces to fasten wood parts together, while bolts use spiral surfaces, nails and bolts may be equivalent structures in the context of fixing wood parts. It is the clear intention of the applicant that any limitation of any of the claims herein is not invoked in paragraph 6 of 35 U.S.C. § 112, except for those in which the claims expressly use the term "device for..." in conjunction with the relevant functions.

Claims

1. A method, comprising: reacting an antistatic agent with at least one aluminum alkyl to form an antistatic complex, wherein the antistatic agent is a fatty acid ester, wherein the alkylaluminum is one or more of triethylaluminum and triisobutylaluminum, and The fatty acid ester is formed by reacting a saturated or unsaturated fatty acid having a length of C6 to C26 with a polyol having one or more acids reacted therewith.

2. The method according to claim 1, further comprising: The antistatic compound is fed into the polymerization process.

3. The method of claim 1, further comprising mixing the antistatic agent with at least one hydrocarbon compound prior to reacting the antistatic agent with the alkylaluminum.

4. A method for using an antistatic agent in a polymerization process, the method comprising: feeding the antistatic agent into the polymerization process, wherein the antistatic agent is a fatty acid ester; Then reacting the antistatic agent with at least one aluminum alkyl, wherein the alkylaluminum is one or more of triethylaluminum and triisobutylaluminum, and The fatty acid ester is formed by reacting a saturated or unsaturated fatty acid having a length of C6 to C26 with a polyol having one or more acids reacted therewith.

5. The method of claim 4, further comprising mixing the antistatic agent with at least one hydrocarbon compound before feeding the antistatic agent into the polymerization process.

6. The method according to 4, wherein the antistatic agent is reacted with the at least one alkyl aluminum to obtain an antistatic complex, wherein the antistatic complex comprises the fatty acid ester, the alkyl aluminum, and one or more reaction products between the fatty acid ester and the alkyl aluminum.

7. The method of claim 6, wherein the one or more reaction products comprise aluminum stearate and / or an aluminum alkyl different from the at least one aluminum alkyl reacted with the antistatic agent.

8. The method according to any one of claims 3 and 5, wherein the hydrocarbon compound is a C3-C6 hydrocarbon.

9. The method according to any one of claims 3 and 5, wherein the hydrocarbon compound is saturated.

10. The method according to any one of claims 3 and 5, wherein the hydrocarbon compound is unsaturated.

11. The method according to any one of claims 1 and 4, wherein the molar ratio of the amount of the antistatic agent relative to the amount of the alkylaluminum is in the range of 1:1 to 1:

200. 12 . The method according to claim 11 , wherein a molar ratio of the amount of the antistatic agent relative to the amount of the alkyl aluminum is in a range of 1:10 to 1:

150. 13 . The method according to claim 12 , wherein a molar ratio of the amount of the antistatic agent relative to the amount of the alkyl aluminum is in a range of 1:50 to 1:

100.

14. The method according to any one of claims 1 and 4, wherein the alkylaluminum is one of triethylaluminum and triisobutylaluminum. 15 . The method according to claim 3 , wherein a mass ratio of the amount of the antistatic agent relative to the amount of the hydrocarbon compound is in the range of 1:10 to 9:

10.

16. The method according to any one of claims 3 and 5, wherein the antistatic agent and the hydrocarbon compound are mixed using a continuous stirred tank reactor or an inline mixer.

17. The process according to any one of claims 2 and 4, wherein the antistatic compound is fed into the polymerization process by a valveless pump.

18. The method according to any one of claims 2 and 4, wherein the polymerization process is a gas phase polymerization.

19. The process according to any one of claims 2 and 4, wherein the polymerization process involves the use of a metallocene or Ziegler-Natta catalyst.

20. The method of any one of claims 2 and 4, wherein the polymerization process polymerizes at least one or more of ethylene, propylene, butene, and hexene.

21. The method of any one of claims 2 and 4, wherein the polymerization process produces a homopolymer.

22. The method of claim 21, wherein the homopolymer is one of polypropylene and polyethylene.

23. The method of any one of claims 2 and 4, wherein the polymerization process produces a copolymer.

24. The method of claim 23, wherein the copolymer is one of a polypropylene random copolymer, a polypropylene heterophasic copolymer, a polypropylene terpolymer, and a linear low density polyethylene.

25. The process according to any one of claims 2 and 4, wherein the antistatic composite is fed into the polymerization process at one or more of a gas phase reactor, a loop reactor, an exit reactor line, a gas phase recycle line, a bag filter or a heat exchanger used to carry out the polymerization process.

26. The process according to any one of claims 2 and 4, wherein the feeding is carried out continuously during the polymerization process.

27. The process according to any one of claims 2 and 4, wherein the antistatic agent is fed into the polymerization process at a rate in an amount ranging from 5 to 1000 ppm by weight relative to the polymer production rate.

28. A polymer prepared by the method of any one of claims 2 to 27, wherein the polymer comprises an antistatic complex comprising one or more reaction products between a fatty acid ester and at least one aluminum alkyl, wherein the alkylaluminum is one or more of triethylaluminum and triisobutylaluminum, and The fatty acid ester is formed by reacting a saturated or unsaturated fatty acid having a length of C6 to C26 with a polyol having one or more acids reacted therewith.

29. An antistatic composite prepared by the method of any one of claims 1, 3 or 6-15.

30. The antistatic compound according to claim 29, further comprising at least one hydrocarbon compound.

Citation Information

Patent Citations

  • Polymerization process

    EP1255783B1

  • Improved gas phase process for the polymerization of olefins

    EP3034519A1

  • Polymerization process in the presence of an antistatic agent

    US20120283369A1

  • Continuous feed of auxiliaries for the polymerization of olefins

    US8017703B2

  • Reactor operability in a gas phase polymerization process

    US8865847B2